Sobre el legado crítico: dos perspectivas sobre la Ilustración - León, Sebastián (2017)
The present essay approaches two different conceptions of Enlightenment and modernity. The first part considers Michel Foucault’s understanding of modernity as an “attitude” or “critical ethos” belonging to that age, that necessarily questions that which we have come to be in various contingent processes (how we have constituted ourselves as subjects); the second part considers Jürgen Habermas’s proposal, which invites us to understand modernity as an “unfinished project”, as a certain potential or rational ideal that is still to be carried out. Towards the end of the essay both stances are confronted, whereby an attempt is made to engage elements retrieved from each in a productive dialogue, and to raise some criticisms and observations regarding the sociohistorical conceptions of each author.